Implementasi Penerapan Etika Bisnis Islam dalam Melakukan Transakasi Jual Beli di Pasar Tradisional: Studi Pasar Pagi 28 Purwoasri Metro Utara - Azahra Eka Putri; Dwi Septi Nuraeni; Lilis Renfiana (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Islamic business ethics can be explained as an understanding of principles that govern and manage businesses by considering norms and morality in line with Islamic values. In Islam, business ethics encompasses conduct in the business world that integrates the values and teachings found in the Qur'an and Hadith into a unified business practice. Buying and selling involve a process where the exchange of goods adheres to values, involving both sellers and buyers who comply with Islamic Sharia principles. The aim of this research is to evaluate the implementation of Islamic business ethics in buying and selling transactions at Pasar Pagi 28 Desa Purwoasri, North Metro District, Metro City. This study is a field research involving direct observation of traders in the market. A qualitative approach is used to descriptively analyze the business ethics behavior applied by traders at Pasar Pagi 28 Purwoasri North Metro, Metro City. The results of this research indicate that in buying and selling transactions in the traditional market of 28 Purwoasri, the five principles of Islamic business ethics, namely Tawhid, Balance/Justice, Accountability, Free will, and Excellence, have been implemented.